New records for the liverwort and hornwort flora of Vietnam, 1 - Pócs T.; Tram N.-K.-T.; He Q.; Katagiri T.; Luong T.-T. (Hungarian Academy of Sciences, 2025)
After the examination of the Cryptogam collection in the Herbarium of the University of Science, Vietnam National University Ho Chi Minh City (PHH), 25 species proved to be new to Vietnam, including one hornwort and 24 liverworts. Among them, four genera: Denotarisia Grolle, Gongylanthus Nees, Leiomitra Lindb. and Lepicolea Dumort. are new records for the country. Diagnostic characters and illustrations are given for some taxa, as well as locality notes and habitat descriptions are provided for each collecting area.